2016
DOI: 10.1039/c5sc04048e
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon constrained peptides – understanding preorganisation and binding affinity

Abstract: Biophysical studies on hydrocarbon constrained peptides reveal induced fit binding and enthalpy–entropy compensation on target protein recognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 57 publications
4
83
1
Order By: Relevance
“…Stapling also does not always improve the binding affinity of the peptide, as observed in several independent studies [40,[95][96][97]. Enthalpy-entropy compensation has recently been invoked to explain these perplexing observations [97]. It is suggested that, because of the presence of backbone hydrogen bonding before binding, the gain in favourable enthalpy upon binding by a stapled peptide is not as significant as that observed with the unstapled peptide.…”
Section: Future Directionsmentioning
confidence: 94%
See 1 more Smart Citation
“…Stapling also does not always improve the binding affinity of the peptide, as observed in several independent studies [40,[95][96][97]. Enthalpy-entropy compensation has recently been invoked to explain these perplexing observations [97]. It is suggested that, because of the presence of backbone hydrogen bonding before binding, the gain in favourable enthalpy upon binding by a stapled peptide is not as significant as that observed with the unstapled peptide.…”
Section: Future Directionsmentioning
confidence: 94%
“…No direct correlation was also found between helical content and cell activity in another study on the targeting of HIV-1 integrase by hydrocarbon stapled peptides [27]. Stapling also does not always improve the binding affinity of the peptide, as observed in several independent studies [40,[95][96][97]. Enthalpy-entropy compensation has recently been invoked to explain these perplexing observations [97].…”
Section: Future Directionsmentioning
confidence: 96%
“…Of these, the use of variant peptides bearing alkenyl glycine residues in the i and i +4 positions constrained through olefin metathesis was shown to be effective in biasing the sequences of variant BCL‐2 BH3 sequences towards the helical conformation . Subsequently, we demonstrated that these peptides bind to their target BCL‐2 proteins through an induced‐fit mechanism but do not elicit enhanced target affinity arising from enthalpy–entropy compensation, as demonstrated by surface plasmon resonance (SPR) and van't Hoff analyses, respectively . Herein, using the anti‐silencing function 1 (ASF1) chaperone as a protein target, we demonstrate the broader applicability of S ‐pentenyl‐glycine variant peptides as substrates for hydrocarbon constraining and further reinforce the notion that constraining the peptide in a bioactive conformation might not lead to increased affinity for the target protein due to enthalpy–entropy compensation.…”
Section: Figurementioning
confidence: 99%
“…[47][48][49][50] Moreover, our own prior studies characterized BH3/BCL-2 family interactions as entropically driven. 20 Whilst the Affimer technology regularly produces binders with Kd in the nanomolar range 36 , here we added multiple layers of screening (inhibition of BH3 binding; compatible with anisotropy and ITC experiments) in addition to panning for high affinity binders. This will naturally lead to an attrition rate where clones that do not meet the criteria are lost, which may explain the slightly lower affinities we observe ( Table 1).…”
Section: Biophysical Analysis Of Affimersmentioning
confidence: 99%
“…In silico and experimental approaches have been used to identify selective sequences for individual BCL-2 family members. [13][14][15][16] Multiple studies have endeavoured to identify chemotypes which mimic the BH3 domains so as to orthosterically inhibit BCL-2/BH3 PPIs including: constrained peptides, [17][18][19][20][21][22][23] peptidomimetics, [24][25][26][27] small molecules [28][29][30][31] and miniature proteins (identified with assistance from biological selection). 32,33 We have used a previously described Affimer library [34][35][36][37][38][39] to identify potent ligands for MCL-1, BCL-xL, BCL-2, BAK and BAX and selective inhibitors of MCL-1 and BCL-xL interactions with cognate BH3 partners.…”
Section: Introductionmentioning
confidence: 99%